Geriatric Rehabilitation Review - Heidi Klingbeil (Association of American Medical Colleges, 2008)
Abstract By 2020, about 20% of the population will be 65 years or older. Of this group, 80% will have musculoskeletal complaints, and 40%-60% will have significant osteoarthritis. The treatment of the pain or functional impairments of older individuals requires a very careful examination of the factors that often operate to decrease the ability of these individuals to recover. Many times, their increased vulnerability to medication side effects or relative malnutrition is overlooked. In addition, rehabilitation of impairments must be tailored to this population, taking into account a different set of tolerances and precautions. This PowerPoint presentation covers the subject of geriatric rehabilitation for rehabilitation medicine residents and residents in other related fields. It can be used to review for board examinations or just to guide one's practice. This material has been highly rated by the residents, fellows, and faculty who have heard portions of it as teaching lectures.